DUALITAS MAKNA SHADHDHAH DALAM NOMENKLATUR QIRA‘AT: Sejarah dan Perkembangannya dalam Qira‘at Shadhdhah - Miftahul Jannah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
This paper examines the history of qiraat, especially qiraat syāzzah. Qiraat syāzzah allegedly arose during the Caliph of Usmān along with the presence of muṣḥaf 'usmānī. However, when there is no syāzzah term itself. Newly in the time of Ibn Mujahid, the term syāzzah is well established in the qiraat discipline as opposed to qira'at sab'ah. From this, questions arise, what is the term used before the time of Ibn Mujahid? How does or how to identify qiraat syāzzah? How do the scholars respond to the term syāzzah popularized by Ibn Mujahid? Therefore, this study is significant not only to see the wealth of the opinion of the Ulama, but to indicate the existence of the continue and change in the area of qiraat syāzzah thinking. The diversity of opinions conveys the shift in the use of the term syāzzah of quantity into quality, which originates from the least reading being da'if.